2021
DOI: 10.3390/en14020339
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Energy Storage System Operation with Capacity P2P Transaction

Abstract: Research on energy storage systems (ESS) is actively aiming to mitigate against the unreliability of renewable energy sources (RES), and ESS operation and management has become one of the most important research topics. Since installing ESS for each user requires high investment cost, a study on cloud ESS gains attention recently. Cloud ESS refers to an ESS that is logically shared by multiple users as if they have their own ESS in their premises. In this paper, we propose a new cloud ESS sharing technique tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The state of charge and state of discharge of CES at the time t, which depends on the amount of remained energy of CES from the time t-1, is calculated by the equation ( 9) and (10) where, η 𝑏𝑐 and η 𝑑𝑏 are charging and discharging efficiency, respectively. In equation (11) where the amount of charge and discharge limitation, in other words, the capacity of the converter is determined by multi-MG managers [45]. Equation (12) provides us with information about the rest of the power in the CES at the last hour of the day.…”
Section: Mathematical Model: Ces Investment Scenario Blockmentioning
confidence: 99%
See 1 more Smart Citation
“…The state of charge and state of discharge of CES at the time t, which depends on the amount of remained energy of CES from the time t-1, is calculated by the equation ( 9) and (10) where, η 𝑏𝑐 and η 𝑑𝑏 are charging and discharging efficiency, respectively. In equation (11) where the amount of charge and discharge limitation, in other words, the capacity of the converter is determined by multi-MG managers [45]. Equation (12) provides us with information about the rest of the power in the CES at the last hour of the day.…”
Section: Mathematical Model: Ces Investment Scenario Blockmentioning
confidence: 99%
“…Energy storage systems operation and management have recently sparked an immense debate. Because the installation of individual energy storage for each end-user needs a high investment cost [11]. Furthermore, overcoming the problem of supply-demand mismatching cannot be easily performed [13].…”
Section: Introduction I Motivationmentioning
confidence: 99%
“…The results of their simulation showed that users profit considerably more from such sharing mechanisms compared to owning individual storage systems. Cloud energy storage is a concept that describes the logical sharing of an ESS by multiple users [11]. A technique that allows peer-to-peer (P2P) capacity sharing among users was studied in [11].…”
Section: Introductionmentioning
confidence: 99%
“…Cloud energy storage is a concept that describes the logical sharing of an ESS by multiple users [11]. A technique that allows peer-to-peer (P2P) capacity sharing among users was studied in [11]. In [12], a cloud energy storage solution for utilizing distributed energy storage systems in microgrids is presented.…”
Section: Introductionmentioning
confidence: 99%
“…The models developed by the authors so far [17] will be supplemented by the key element for these considerations-batteries (energy stores) [28]-which may determine not only the character and structure of emerging cooperatives but also, in some cases, become a factor determining their profitability [29,30]. The research objectives set by the authors are the analysis and assessment of: (i) whether, through an appropriate choice of generation sources and an energy storage facility, it is possible to avoid consuming energy from the grid (outside the virtual network deposit) [17,31], which makes it possible to avoid capacity fees; (ii) whether it is worth installing high-capacity energy storage, or whether a measurable effect of improving the optimization target can already be achieved by storage with a lower capacity and power; (iii) to what extent it is possible to estimate the volumetric savings in consuming energy from the virtual network deposit through the use of an actual energy store; and (iv) whether it is reasonable to build an actual store for each cooperative and, if not, which cooperatives it would be reasonable for.…”
Section: Introductionmentioning
confidence: 99%